Naravni procesi v svetih knjigah - Zorn, Matija (Geografski vestnik, 2007)
In the article several quotations about natural processes from the Bible, Koran and Talmud and some other religious-philosophical treaties are explained. The descriptions are precise and can be correlated to historical records on one hand while some of them use the description of natural processes in order to describe theological aspects on the other. In this case one can not find suitable natural-historical explanation of the event. Our assessment of the comprehension of natural processes by the ancient peoples ofthe Near East is based on scientific literature and the records in the holy books. We substantiate the explanations with contemporaneous knowledge on natural processes and with the chronology of natural events, known from other sources than holy books. We discuss the following natural phenomena and processes, mentioned in holy books: earth, earthquake, landslide, volcano, ore deposits, geothermic degree, fault, mountain, erosion, isolate rock, sink, storm, spring, flood, drought, natural gas deposits.
Keywords: zgodovinska geografija; geomorfologija; geomorphology; naravni pojavi; procesi; interpretacija; Sveto pismo; Bible; Quran; Koran; Talmud